Tissue-specific expression patterns of microRNA during acute graft-versus-host disease in the rat. - Dasaradha Jalapothu; Margherita Boieri; Margherita Boieri; Rachel E Crossland; Pranali Shah; Isha Ammar Butt; Jean Norden; Ralf Dressel; Anne Mary Dickinson; Marit Inngjerdingen; Marit Inngjerdingen (Frontiers in Immunology, 2016)
MicroRNAs (miRNA) have emerged as central regulators of diverse biological processes, and contribute to driving pathology in several diseases. Acute graft-versus-host disease (aGvHD) represents a major complication after allogeneic hematopoietic stem cell transplantation, caused by alloreactive donor T cells attacking host tissues leading to inflammation and tissue destruction. Changes in miRNA expression patterns occur during aGvHD, and we hypothesized that we could identify miRNA signatures in target tissues of aGvHD that may potentially help understand the underlying molecular pathology of the disease. We utilized a rat model of aGvHD with transplantation of fully MHC-mismatched T cell depleted bone marrow, followed by infusion of donor T cells. The expression pattern of 423 rat miRNAs was investigated in skin, gut, and lung tissues and intestinal T cells with the NanoString hybridization platform, in combination with validation by quantitative PCR. MHC-matched transplanted rats were included as controls. In the skin, up-regulation of miR-34b and down-regulation of miR-326 was observed, while in the intestines we detected down-regulation of miR-743b and a trend towards down-regulation of miR-345-5p. Thus tissue-specific expression patterns of miRNAs were observed. Neither miR-326 nor miR-743b has previously been associated with aGvHD. Moreover, we identified up-regulation of miR-146a and miR-155 in skin tissue of rats suffering from aGvHD. Analysis of intestinal T cells indicated 23 miRNAs differentially regulated between aGvHD and controls. Two of these miRNAs were differentially expressed either in skin (miR-326) or in intestinal (miR-345-5p) tissue. Comparison of intestinal and peripheral blood T cells indicated common dysregulated expression of miR-99a, miR-223, miR-326, and miR-345-5p. Analysis of predicted gene targets for these miRNAs indicated potential targeting of an inflammatory network both in skin and in the intestines that may further regulate inflammatory cytokine production. In conclusion, comprehensive miRNA profiling in rats suffering from aGvHD demonstrate tissue specific differences in the expression patterns of miRNA that may not be detected by profiling of peripheral blood T cells alone. These tissue specific miRNAs may contribute to distinct pathologic mechanisms, and could represent potential targets for therapy.